From social curse to social cure: A self‐help group community intervention for people affected by leprosy in Nepal. (22nd February 2021) - Jay, Sarah; Winterburn, Michael; Choudhary, Ramesh; Jha, Kiran; Sah, Arbind Kumar; O'Connell, Brenda H; O'Donnell, Aisling T; Moynihan, Andrew B; Muldoon, Orla T
Abstract: Leprosy is endemic in Nepal and disproportionately affects the most marginalized. Leprosy related stigma can be characterized as a social curse, because those affected are excluded from group life and social participation which has severe implications for psychological health. The Nepal Leprosy Trust run a community‐based self‐help group intervention that aims to develop a new empowered identity to re‐establish access to multiple group memberships' through social participation. In this applied cross‐sectional study, informed by the Social Identity Model of Identity Change, we assess this intervention. Participants ( N = 98) were members of self‐help groups in 10 rural villages in Nepal, and completed measures of self‐help group identification, access to multiple groups, internalized stigma and well‐being. Mediation models indicated that self‐help group identification was indirectly linked to reduced stigma and increased well‐being through access to multiple groups. Supporting the Social Identity Model of Identity Change, we present novel evidence that group‐based interventions can offer new valued identities that link to social cure resources, even in the most adverse circumstances. Please refer to the Supplementary Material section to find this article's Community and Social Impact Statement .